The Best of the Grammarians : Aristarchus of Samothrace on the Iliad - Schironi, Francesca (Book collections on Project MUSE., 2018)
This book will be valuable to classicists and philologists interested in scholarship on Aristarchus, Homer and Homeric criticism in antiquity, the history of Greek culture, Hellenistic scholarship, and ancient literary criticism.